Condition-specific competition governs the geographic distribution and diversity of ectoparasites - Malenke, J R; Newbold, N; Clayton, D H (The American naturalist, 2011)
Understanding how environmental parameters interact to govern species distributions is a shared goal of ecology and biogeography. Biotic and abiotic conditions can change distributions by affecting the nature of interspecific interactions. Although documented in free-living systems, this context dependency has been neglected in parasite interactions. We investigated the influence of condition-specific competition on the specificity of two species of feather lice (Phthiraptera: Ischnocera) that share a host, the mourning dove (Zenaida macroura). We show that relative humidity restricts the range of one species, Columbicola macrourae3 (i.e., the C. macrourae lineage found on mourning doves), to the more humid eastern United States. The second species, Columbicola baculoides, an arid-adapted species, is restricted to drier regions of the western United States by C. macrourae3, which outcompetes it in experiments. Thus, arid conditions in the West provide C. baculoides with a climatic refuge from the competitively superior C. macrourae3, effectively doubling parasite diversity on one host species. These results support the hypothesis that abiotic factors can determine species distributions on the stressful end of an environmental gradient while interspecific competition governs distributions at the benign end. The balance between these factors is subject to change as environmental conditions change, even if the host distribution remains unaffected.